Social Construction of TechnologyA review of Forces of Production: A Social History of Industrial Automation by NobleDavid F., New York: Alfred A. Knopf, Inc., 1984, 409 pp., $22.95, cloth. - Nord, Walter R. (Academy of Management Review, 1986)
The article presents a review of the book “Forces of Production: A Social History of Industrial Automation,” by David F. Noble.